2006
DOI: 10.1074/jbc.m606601200
|View full text |Cite
|
Sign up to set email alerts
|

Neuralized-2 Regulates a Notch Ligand in Cooperation with Mind Bomb-1

Abstract: Mutations in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 50 publications
5
61
1
2
Order By: Relevance
“…Its critical regulation of NotchDelta signaling alone incorporates it into almost every aspect of nervous system development (6,10,(55)(56)(57)(58)(59)(60). More recently, an interactome study revealed that it also plays a role in the equally vital Wnt signaling pathway (18).…”
Section: Discussionmentioning
confidence: 99%
“…Its critical regulation of NotchDelta signaling alone incorporates it into almost every aspect of nervous system development (6,10,(55)(56)(57)(58)(59)(60). More recently, an interactome study revealed that it also plays a role in the equally vital Wnt signaling pathway (18).…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, it is well established that the ubiquitin ligase activities of Neuralized and/or Mindbomb1 are needed for endocytosis, activation, and degradation of Notch ligands, all processes likely dependent on ubiquitination of the ligand intracellular domains (12,13,15,17,37). Furthermore, ectopic expression of a second murine Neur paralog, Neurl2, was shown to increase ubiquitination of Dll1 in transfected cells (22), and a Xenopus Neurl ortholog was shown to promote ubiquitination of in vitro translated Xenopus Delta1 (38). Nevertheless, until the present work it had not been rigorously demonstrated, using a purified enzyme system, that a Neuralized protein directly supports ubiquitination of a ligand.…”
Section: Discussionmentioning
confidence: 99%
“…□ S The on-line version of this article (available at http://www.jbc.org) contains supplemental ubiquitination in cells. In addition, Neurl2 functioned cooperatively with Mib1 to promote endocytosis of XDelta to Hrs (hepatocyte growth factor-regulated tyrosine kinase substrate)-positive early endosomes (22); however, unequivocal evidence that Dll1 is a direct target of Neurl2 ubiquitin ligase activity is lacking. Although Neurl1 has also been shown to exhibit a nonspecific ubiquitin ligase activity in vitro (22), putative Neurl1 substrates have not been identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two structurally distinct E3 ubiquitin ligases, Neuralized (Neur) and Mind bomb (Mib), are known to regulate the endocytosis of Notch ligands in Drosophila and zebrafish, respectively (16,17). In mammals, 2 Neur homologs, Neur1 (18,19) and Neur2 (20), and 2 Mib homologs, Mind bomb-1 (Mib1) (21) and Mib2 (22), have been identified. Although all 4 E3 ubiquitin ligases are known to induce the endocytosis of Notch ligands in vitro, only Mib1 has an obligatory role in the activation of Jag-as well as Dll-mediated Notch signaling in mammalian development, while Neur1, Neur2, and Mib2 are dispensable (23).…”
Section: Introductionmentioning
confidence: 99%